Real-world incidence and burden of adverse events among non-metastatic prostate cancer patients treated with secondary hormonal therapies following androgen deprivation therapy. (2nd April 2020) - Shah, Anuj; Shah, Ruchit; Kebede, Nehemiah; Mohamed, Ateesha; Botteman, Marc; Waldeck, Reg; Hussain, Arif
Abstract: Aims: To describe the incidence and identify prognostic factors of central nervous system (CNS) adverse events (AEs) and any AEs (CNS, skin rash, or fracture) and evaluate the healthcare resource utilization (HCRU), direct medical costs, and therapy discontinuation associated with these AEs among non-metastatic prostate cancer (nmPC) patients who received secondary hormone therapies. Methods and results: nmPC patients who had initiated secondary hormonal therapy with enzalutamide, bicalutamide, or abiraterone ≥1 year after androgen deprivation therapy (ADT) were identified in the MarketScan database. Survival analyses were used to describe the incidence of CNS or any AEs. Annual HCRU and costs were compared across patient groups (CNS AE vs no CNS AE; any AE vs no AE) using propensity score weighted generalized linear models. Multivariate Cox proportional hazards models were used to identify AE predictors and compare risks of discontinuation. Results: The analysis included 532 patients who initiated secondary hormonal therapies, among whom 201 (38%) and 244 (46%) experienced a CNS AE and any AE, respectively. Median times to CNS AE and any AE from therapy initiation were 17.90 and 11.00 months, respectively. Predictors of any AE were any AE in the baseline period (≤6 months before starting therapy), Charlson Comorbidity Index (CCI) score (1 vs 0), surgical castration, and older age. Predictors of CNS AEs were CNS AE in the baseline period and CCI score (1 vs 0). CNS and any AEs were associated with significantly higher HCRU. CNS AEs were associated with significantly higher incremental total medical costs ($18, 522). CNS AEs and any AEs significantly increased therapy discontinuation risk by 48% and 38%, respectively. Conclusions: AEs increase the economic burden and therapy discontinuation among nmPC patients receiving secondary hormonal therapies subsequent to ADTs. These patients should be carefully evaluated for AEs to reduce therapy discontinuation, HCRU, and direct medical costs.